Direct and Indirect Effects of Maternal, Paternal, and Offspring Genotypes: Trio-GCTA - Eilertsen, Espen Moen; Jami, Eshim Shahid; McAdams, Tom A.; Hannigan, Laurie J.; Havdahl, Alexandra S.; Magnus, Per; Evans, David M.; Ystrom, Eivind (Behavior genetics, 2021)
Indirect genetic effects from relatives may result in misleading quantifications of heritability, but can also be of interest in their own right. In this paper we propose Trio-GCTA, a model for separating direct and indirect genetic effects when genome-wide single nucleotide polymorphism data have been collected from parent-offspring trios. The model is applicable to phenotypes obtained from any of the family members. We discuss appropriate parameter interpretations and apply the method to three exemplar phenotypes: offspring birth weight, maternal relationship satisfaction, and paternal body-mass index, using real data from the Norwegian Mother, Father and Child Cohort Study (MoBa).